2006
DOI: 10.1530/eje.1.02229
|View full text |Cite
|
Sign up to set email alerts
|

Adiponutrin gene is regulated by insulin and glucose in human adipose tissue

Abstract: Objective: Adiponutrin is a new transmembrane protein specifically expressed in adipose tissue. In obese subjects, short-or long-term calorie restriction diets were associated with a reduction in adiponutrin gene expression. Adiponut.rin mRNA level was previously shown to be negatively correlated with fasting glucose plasma levels and associated with insulin sensitivity of non-diabetic obese and nonobese subjects. The purpose of the present work was to get more insight into the regulation of adiponutrin gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 35 publications
2
53
0
3
Order By: Relevance
“…Recent findings by our group and others indicate that, despite being a WAT-derived protein, adiponutrin expression is not elevated in obese subjects (Liu et al 2004, Moldes et al 2006. Furthermore, fasting adiponutrin expression as well as insulin-stimulated increase in adiponutrin expression were reduced in obese type 2 diabetic subjects when compared with controls (Moldes et al 2006).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Recent findings by our group and others indicate that, despite being a WAT-derived protein, adiponutrin expression is not elevated in obese subjects (Liu et al 2004, Moldes et al 2006. Furthermore, fasting adiponutrin expression as well as insulin-stimulated increase in adiponutrin expression were reduced in obese type 2 diabetic subjects when compared with controls (Moldes et al 2006).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, fasting adiponutrin expression as well as insulin-stimulated increase in adiponutrin expression were reduced in obese type 2 diabetic subjects when compared with controls (Moldes et al 2006). Therefore, the regulation of adiponutrin expression in human may be altered by reduced insulin sensitivity and altered regulation of WATderived proteins in relation to insulin signaling and action in states like type 2 diabetes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although its putative role in metabolic disease development has only recently started to be explored, various genome-wide association studies have identified the Pnpla3 gene to be associated with liver-related phenotypes (Romeo et al 2008, Yuan et al 2008, Kotronen et al 2009). Since it is up-regulated in response to feeding and downregulated in the fasted state, a potential role for Pnpla3 in lipid storage has been suggested (Baulande et al 2001, Lake et al 2005, Moldes et al 2006, Wilson et al 2006. Furthermore, the transcription factors SREBPs, PPARg and ChREBP have been shown to mediate increased expression of the Pnpla3 gene (Baulande et al 2001, Polson & Thompson 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Indétectable à jeun, elle est très fortement augmentée après une prise alimentaire [31]. L'insuline et le glucose induisent l'expression de l'adiponutrine [32] qui est surexprimée dans des modèles murins d'obésité [31] ainsi que chez des patients obèses ou insulinorésistants [32]. La protéine est localisée au niveau des structures membranaires du cytoplasme comme l'appareil de Golgi ou le réticulum endoplasmique, site principal de synthèse des lipides dans les cellules de mammifères [31].…”
Section: Pnpla1 4 Etunclassified